Theatre techniques for conflict management: a workshop for college freshmen orientations - Morrow, Cale Joseph (Kansas State University, 2021)
A common problem among incoming college freshman is an inability to deal with conflict in their everyday lives. This is due to insufficient training during their primary education. The factors that make current training insufficient revolve around overly complex training practices and a lack of soft skills. To correct this problem, this report proposes the combination of select theatre techniques to be synthesized with current conflict management training practices. This report starts with an examination of the problems that exist with current training practices, followed by a literature review consisting of the techniques proposed as solutions, and ending with a module-based example of what this type of training would look like during actual implementation. A discussion of future plans for the research, including a method by which to measure its long-term efficacy, is also included.
Keywords: Conflict management; Theatre